Tévedés jogtörténeti fejlődésének egyes állomásai, különös tekintettel Bernolák Nándor tévedés tanára - Mónusné Kiss, Katalin (Debreceni Jogi Műhely, 2005)
I examine one of the grounds for the preclusion of culpability and grounds for the termination of culpability: error. Grounds for the preclusion of culpability are the followings: infancy, abnormal mental condition, constraint and menace, error, negligible degree of danger to society of an act, self-defence, extreme necessity (emergency), absence of private motion, other grounds defined in the Act. Grounds for the termination of culpability are: the death of the perpetrator, prescription, remission, cessation or becoming negligible of the dangerousness for society of the act, other grounds defined in the Act.Grounds for the preclusion of culpability and grounds for the termination of culpability mean that culpability shall be precluded.Error - as an obstacle of the preclusion of culpability – is not as usual as other grounds for the preclusion of culpability, for example: insane mental state, constraint or menace. Error means - 27. § of the Hungarian Criminal Code – that the perpetrator shall not be punishable for a fact of which he was not aware on perpetration. The person, who commits an act in the erroneous hypothesis that it is not dangerous for society and who has reasonable ground for this hypothesis, shall not be punishable. Error shall not exclude culpability, if it is caused by negligence and the law also punishes perpetration deriving from negligence.I examine error’s ruling from Roman law to now days. One of the most important books was written by Nandor Bernolak: The Error doctrine. I succeeded Bernolak’s method to search how error was regulated in different ages. Bernolak wrote his essay in 1910, so he described the rules of error as it appeared in Code Csemegi. I follow his method during the examination of 1950.:II. Criminal Code of General Part, 1961. IV. Criminal Code and finally 1978. IV. Criminal Code.I found many differences and similarities between Criminal Codes, Propositions, and finally I compiled a table about the changes of the development in error’s legal history.There is a rule that is known generally from Roman law: „ignorantia facti, non iuris excusat”, which means: ignorance of the law means no excuse.